2008
DOI: 10.1016/j.envres.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of the US National Health Interview Survey to air monitoring data: An evaluation of different strategies

Abstract: The goal of this study is to describe linkages between the National Health Interview Survey (NHIS) and Environmental Protection Agency (EPA) air monitoring data, specifically how the linkage method affects characteristics and exposure estimates of study samples and estimated associations between exposure and health. In the USA, nationally representative health data are collected in the NHIS and annual air quality data are collected by the EPA. The linkage of these data for research is not straightforward and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We chose to base our estimate of monitored pollutant levels on monitors within 20 miles (32.2 km), based on the work of Parker 47 who linked air pollution estimates for NHIS participants based on an average of 1) all monitors within the county, 2) monitors within a 5 mile radius of the participant census block group, and 3) monitors within 20 miles (32.2 km) of the participant census block group. Parker 47 suggested that these methods gave similar association results but have tradeoffs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to base our estimate of monitored pollutant levels on monitors within 20 miles (32.2 km), based on the work of Parker 47 who linked air pollution estimates for NHIS participants based on an average of 1) all monitors within the county, 2) monitors within a 5 mile radius of the participant census block group, and 3) monitors within 20 miles (32.2 km) of the participant census block group. Parker 47 suggested that these methods gave similar association results but have tradeoffs.…”
Section: Discussionmentioning
confidence: 99%
“…Parker 47 suggested that these methods gave similar association results but have tradeoffs. Linking air pollution estimates to national survey data sets with finer spatial resolution reduces measurement error but also reduces sample size.…”
Section: Discussionmentioning
confidence: 99%
“…PM 10 and PM 1 were measured during the days between time 1 and time 2, using a GRIMM 1100 light‐scattering dust analyzer (Grimm Technologies, Douglasville, GA, USA). The fractions considered for this study were PM 1 and coarse particles, defined as the difference between PM 10 and PM 1 [25]. During the three working days between time 1 and time 2, each of the study subjects recorded the time spent in each of the work areas in a personal log.…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, more precise exposure measures would be available for each child, either from personal monitoring or finer spatial scales, which would lead to more precise effect estimates. With this survey, there is a substantial trade-off between criteria for proximity of monitors and the sample size and composition of the available data (Parker et al 2008a, 2008b). In this case, the results using the substantially smaller samples within 5 miles of a pollution monitor were remarkably similar to the primary results presented.…”
Section: Discussionmentioning
confidence: 99%